Answer:
x = 12
Explanation:
To solve this and show your work, you have to start of with the equation (3x - 6) = 30.
You then have to add 6 to both sides like this:
![(3x - 6) = 30 \\ \: \: \: \: \: \: \: \: \: \: + 6 \: \: \: \: \: + 6](https://img.qammunity.org/2022/formulas/mathematics/high-school/lgexpmy23vix37mjcuann5rr202unl4rmg.png)
So then the 6 is cancelled out, and you are left with
3x = 36.
Now you just have to divide both sides by 3 like this:
![(3x)/(3) = (36)/(3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/zzyih5ee2yjlmhvdrs05l1d1uju0543d2z.png)
Which cancels 3 out, and you are left with
x = 12.